DABCO catalyzed unusual formal [4 + 2] cycloaddition of 3-acyl(or alkoxycarbonyl)-1, 4-enediones with 2, 3-butadienoates: effective access to highly functionalized pyrans. Issue 71 (13th July 2016) - Meng, Xiang-Suo; Jiang, Shan; Xu, Xiao-Yun; Wu, Qiang-Xian; Gu, Yu-Cheng; Shi, De-Qing
Abstract : A convenient and efficient DABCO-catalyzed formal [4 + 2] cycloaddition of 3-acyl(or alkoxycarbonyl)-1, 4-enediones with 2, 3-butadienoates is presented. Abstract : A convenient and efficient DABCO-catalyzed formal [4 + 2] cycloaddition of 3-acyl(or alkoxycarbonyl)-1, 4-enediones with 2, 3-butadienoates is presented. This transformation takes advantage of mild conditions, wide substrate scope and significant functional group tolerance as well as excellent regioselectivity, which makes this method powerful for one-pot synthesis of highly functionalized pyrans in moderate to excellent yields.